1988
DOI: 10.1017/s0033291700008266
|View full text |Cite
|
Sign up to set email alerts
|

Response to drugs in schizophrenia: the influence of family history, obstetric complications and ventricular enlargement

Abstract: SynopsisA prospective study of antipsychotic drug treatment showed no difference in response between schizophrenic in-patients with or without a familial predisposition to the illness (N = 53). All patients received at least 600 mg chlorpromazine equivalents antipsychotic medication for 6 weeks. Ventricle brain ratios, ratings of cortical sulcal widening and a history of obstetric complications also failed to account for the variability, but early age of onset was associated with unsatisfactory response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1995
1995
2007
2007

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…Patient in that study had an average length of illness between 15 and 20 years and the measure of Norman et al The Journal of Nervous and Mental Disease • Volume 195, Number 10, October 2007 treatment response did not provide a clear separation of positive and negative symptoms. Several other past studies that have examined treatment outcome as a function of family history do not focus on first-episode patients and/or do allow a separate assessment of positive and negative symptoms (e.g., Chanpattana and Chakrabhand, 2001;Feldman et al, 2001;Ganev 2000;Nimgaonkar et al, 1988;Silverman et al, 1987;Verdoux et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patient in that study had an average length of illness between 15 and 20 years and the measure of Norman et al The Journal of Nervous and Mental Disease • Volume 195, Number 10, October 2007 treatment response did not provide a clear separation of positive and negative symptoms. Several other past studies that have examined treatment outcome as a function of family history do not focus on first-episode patients and/or do allow a separate assessment of positive and negative symptoms (e.g., Chanpattana and Chakrabhand, 2001;Feldman et al, 2001;Ganev 2000;Nimgaonkar et al, 1988;Silverman et al, 1987;Verdoux et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Because these potential correlates of family history can in their own right be related to premorbid characteristics or course of illness (Nimgaonkar et al, 1988;Riecher-Rössler and Häfner, 2000), it is advisable to control for them if we are to clearly examine the impact of family history per se. In the current article we report the results of a comparison of family history positive and negative cases of schizophrenia spectrum disorder in a first-episode program using a case comparison method matching for sex and age of onset.…”
mentioning
confidence: 99%
“…Early onset has been associated with poor response to neuroleptic treatment [15][16][17][18] and worse long-term outcome. 19,20 Häfner et al 1989 21 found that, specifically for men, symptom severity decreased with later onset.…”
Section: Figurementioning
confidence: 99%
“…It now seems that individuals who present with negative symptoms may not only have positive symptoms at the same time, but they may relapse with predominantly positive symptoms (Kay et al, 1986). Positive symptoms do appear to respond better than negative symptoms to antipsychotics, but there has been little empirical evidence of a differential response between patients with and without CT abnormalities (Nimgaonkar et al, 1988). Nevertheless, there appears to be a relationship between negative symptoms, intellectual impairment and neurological signs, and between each of these and enlarged ventricles (Crow, 1985).…”
Section: Determining the Validity Of Different Definitionsmentioning
confidence: 99%